2004
DOI: 10.1111/j.1476-5810.2004.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Results from the treatment of advanced stage squamous cell carcinoma of the nasal planum in cats, using a combination of intralesional carboplatin and superficial radiotherapy: a pilot study

Abstract: Six cats with an advanced stage squamous cell carcinoma (SCC) of the nasal planum were treated with a combination of superficial radiotherapy and intralesional carboplatin therapy. This multimodality protocol was well tolerated by the majority of cats and resulted in complete responses in all cats (100%). Median follow-up for all cats is 268 days, and the median time-to-recurrence, time-to-progression and overall survival have not yet been reached. Our study, although limited in number of animals and with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…The cohort was too small to allow definitive conclusion for tumor control and, the antitumor effect of FLASH-RT was evaluated as a secondary endpoint. SCC of the nasal planum is an appropriate model for which surgery can be functionally devastating and for which Conv-RT is commonly used in clinical practice, albeit with relatively poor outcome and severe toxicity (16,17,24). An obvious interest of FLASH-RT is the possibility to use a single curative fraction, whereas Conv-RT requires relatively complex logistics with several fractions and multiple anesthesias that impair the cats' quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort was too small to allow definitive conclusion for tumor control and, the antitumor effect of FLASH-RT was evaluated as a secondary endpoint. SCC of the nasal planum is an appropriate model for which surgery can be functionally devastating and for which Conv-RT is commonly used in clinical practice, albeit with relatively poor outcome and severe toxicity (16,17,24). An obvious interest of FLASH-RT is the possibility to use a single curative fraction, whereas Conv-RT requires relatively complex logistics with several fractions and multiple anesthesias that impair the cats' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is mostly restricted to early-stage tumors (Tis and T1) because of the poor cosmetic and functional outcome in more advanced cases (13). Brachytherapy has been used with favorable results in Tis/T1 tumors (14,15), whereas fractionated orthovoltage irradiation has also been used for relatively superficial invasive tumors (16,17). Similarly, fractionated radiotherapy using electron (18,19) or proton beams (20) at conventional dose rates showed 1-year progression-free survival (PFS) rates ranging from 50% to 60% in locally advanced cases.…”
Section: Introductionmentioning
confidence: 99%
“…This is not unexpected since many therapies studied report a higher success rate in early stage SCC lesions compared to more advanced lesions (Carlisle & Gould 1982, Withrow & Straw 1990, Peaston et al 1993, Theon et al 1995, Cunha et al 2010. Alternative treatments, such as nasal planum resection (Lana et al 1997) or combined intralesional carboplatin and radiotherapy (de Vos et al 2004) would be expected to be superior for treatment of extensive invasive SCC of the nasal planum.…”
Section: Discussionmentioning
confidence: 99%
“…Additional tumours may arise on the nasal planum as a consequence of the entire area being exposed to UV light. Numerous treatments have been described including hyperthermia, external beam radiotherapy, nasal planum resection, cryotherapy, photodynamic therapy, intralesional chemotherapy, combined radiotherapy and intralesional chemotherapy, strontium-90 plesiotherapy and electrochemotherapy (Grier et al 1980, Carlisle & Gould 1982, Withrow & Straw 1990, Clarke 1991, Peaston et al 1993, Theon et al 1996, Lana et al 1997, de Vos et al 2004, Goodfellow et al 2006, Hammond et al 2007, Spugnini et al 2009). Many of these treatments are highly effective, however, not all are available in general veterinary practice because of their associated expense and the need for specialised equipment and training.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies refer to intratumoural cisplatin delivery to treat solid tumours in the canine and equine species 46–53 . Further examples include intralesional bleomycin in dogs for the treatment of recurrent acanthomatous epulis, 54 intralesional carboplatin to treat feline squamous cell carcinoma of the nasal planum 55,56 and methotrexate and carmustine implants to treat oral melanoma in dogs 47 . Recently, Stewart et al 57 reported a protocol similar to that of the present study to treat sarcoids in the equine species.…”
Section: Discussionmentioning
confidence: 99%